2017
DOI: 10.1037/abn0000231
|View full text |Cite
|
Sign up to set email alerts
|

Narrative production in children with autism spectrum disorder (ASD) and children with attention-deficit/hyperactivity disorder (ADHD): Similarities and differences.

Abstract: The present study focuses on the similarities and differences in language production between children with autism spectrum disorder (ASD) and children with attention-deficit/hyperactivity disorder (ADHD). In addition, we investigated whether Theory of Mind (ToM), working memory, and response inhibition are associated with language production. Narratives, produced by 106 Dutch-speaking children (36 with ASD, 34 with ADHD, and 36 typically developing) aged 6 to 12 during ADOS assessment, were examined on several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
69
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 64 publications
13
69
3
4
Order By: Relevance
“…In contrast to our initial predictions, both the autistic and TD groups' overall recall was similarly negatively impacted when the event's narrative structure was lost, indicating a lack of group differences at the encoding stage. While there is robust evidence that the comprehension and production of narratives can be difficult for autistic individuals (e.g., Boucher, 1981;Diehl et al, 2006;Hilvert, et al, 2016;Kuijper, Hartman, Bogaerds-Hazenberg, & Hendriks, 2017;Lee et al, 2018;Losh & Capps, 2003;Loveland et al, 1990;McCabe et al, 2013), there is also some limited evidence suggesting that autistic individuals can sometimes utilise narratives to enhance their encoding and subsequent retrieval. For example, in contrast to previous findings of no enhancement of emotionally arousing content on recall of static stimuli such as words , sentences (Beversdorf et al, 1998) and images in ASD (Deruelle, Hubert, Santos, & Wicker, 2008), over two experiments Maras et al (2012) found that emotionally arousing stories were remembered better (and forgotten less) than neutral events by both autistic and TD participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our initial predictions, both the autistic and TD groups' overall recall was similarly negatively impacted when the event's narrative structure was lost, indicating a lack of group differences at the encoding stage. While there is robust evidence that the comprehension and production of narratives can be difficult for autistic individuals (e.g., Boucher, 1981;Diehl et al, 2006;Hilvert, et al, 2016;Kuijper, Hartman, Bogaerds-Hazenberg, & Hendriks, 2017;Lee et al, 2018;Losh & Capps, 2003;Loveland et al, 1990;McCabe et al, 2013), there is also some limited evidence suggesting that autistic individuals can sometimes utilise narratives to enhance their encoding and subsequent retrieval. For example, in contrast to previous findings of no enhancement of emotionally arousing content on recall of static stimuli such as words , sentences (Beversdorf et al, 1998) and images in ASD (Deruelle, Hubert, Santos, & Wicker, 2008), over two experiments Maras et al (2012) found that emotionally arousing stories were remembered better (and forgotten less) than neutral events by both autistic and TD participants.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond experimental memory paradigms, most autistic people also experience some degree of difficulty in their ability to construct and relate a coherent narrative (Tager-Flusberg, Paul, & Lord, 2005). While generally not differing from language-matched TD individuals on basic aspects of narrative, such as the identification of the main elements of an event (Beaumont & Newcombe, 2006;Capps, Losh, & Thurber, 2000;Hilvert, Davidson, & Gámez, 2016;Hogan-Brown, Losh, Martin, & Mueffelmann, 2013;Losh & Capps, 2003;Tager-Flusberg & Sullivan, 1995), autistic individuals' narratives often lack causation and coherence, particularly with regards to temporality and the causal connection of plot points (e.g., Capps et al, 2000;Diehl, Bennetto, & Young, 2006;Hilvert et al, 2016;King, Dockrell, & Stuart, 2014;Kuijper, Hartman, Bogaerds-Hazenberg, & Hendriks, 2017;Lee et al, 2018;Losh & Capps, 2003;Losh & Gordon, 2014;McCabe, Hillier, & Shapiro, 2013;Tager-Flusberg, 2000). It has been suggested that these narrative difficulties may be explained in part by difficulties in considering the needs and perspectives of the listener (e.g., Baron-Cohen, 1988;Colle, Baron-Cohen, Wheelwright, & van der Lely, 2008;Bruner & Feldman, 1993;Goldman, 2008;Hilvert et al, 2016;Tager-Flusberg, 1995;Tager-Flusberg & Sullivan, 1995) as well as in generating, strategically planning and organizing one's recall of an event (Barnes & Baron-Cohen, 2012).…”
mentioning
confidence: 99%
“…In sum, research on the relationship between working memory and story creating in preschoolers is sparse, and the results of existing studies are not conclusive due, mainly, to differences in tasks used to elicit narration (retelling, composing a story based on one or a series of pictures) and in populations (atypically developing children and matched on different factors peers [38,41,42]), which limits the generalizability of the results to typically developing children (without language delays). Finally, in the majority of the above-mentioned studies, the two components (visual and verbal) of working memory were analyzed conjunctly, which does not allow to evaluate their respective contribution to the development of spontaneous language production.…”
Section: Relationship Between Language Development and Working Memorymentioning
confidence: 99%
“…Although there is a growing body of research on the relationship between working memory and language development, only a few studies thus far have examined the relationship between working memory and children's ability to produce a spontaneous monologue speech, as, for example, when children compose a story (a narrative) [35], or retell it [36]. Among these studies, the overwhelming majority examined this relationship in atypically developing populations or in a comparative paradigm (e.g., atypically vs. typically developing children) [33,[37][38][39][40][41][42]. For example, Dodwell and Bavin [38] reported a significant relationship between various working memory tasks and children's capacity to retell and to create a story (based on pictures).…”
Section: Relationship Between Language Development and Working Memorymentioning
confidence: 99%
“…ADHD and ASD deviate in terms of narrative production in children; children with ASD performing worse on narrative production, whereas children with ADHD perform better than typically developing (TD) children in terms of their mean Z-scores for emotional and cognitive terms in lexical semantics. In contrast, children with ASD and ADHD are similar in some ways; e.g., in measures of mean length of utterance, they both perform poorly compared with TD children (Kuijper et al, 2017).…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%